PEMECAHAN MASALAH KINEMATIKA KE DEPAN PADA TANGAN ROBOT n-SEGMEN - Bambang Hendriya Guswanto; Alisya Masturoh; Triyani Triyani (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2020)
This article discusses a forward kinematics space for a robot’s hand with n arms in two dimensional Euclid space. The kinematics space of the robot’s hand is obtained by employing some geometrical transformations, those are rotation and dilatation. The solution of this problem is represented by a function corresponding a set of pairs of hinge configuration with a set of pairs of robot’s position and hand endpoint direction.